Structural Modeling of Knowledge, Attitude, and Prevention Practices of COVID-19 Among Online Food Delivery Services in Greater Jakarta Area, Indonesia - Mutaqin, Muhammad Zakki; Dewanti-Hariyadi, Ratih; Nurtama, Budi (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2024)
This study aims to develop a structural model to assess knowledge, attitudes, and COVID-19 preventive practices among food handlers (FH) and food delivery workers (FDW) in Greater Jakarta, Indonesia. Given the region's high population density, the risk of COVID-19 transmission is heightened, making preventive practices essential. Data were collected from 675 respondents using a questionnaire consisting of 36 items. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). Results revealed that both knowledge (β= 0.959 for FH; β= 0.756 for FDW; p<0.05) and attitude (β= 0.546 for FH; β= 0.410 for FDW; p<0.05) positively impacted COVID-19 preventive practices. Attitude emerged as a crucial predictor, explaining a higher variance in FH prevention practices (R²= 0.346) than in FDW (R²= 0.174). The findings underscore the importance of strengthening attitudes toward preventive measures like hand washing, mask-wearing, and physical distancing, particularly among FDWs, to enhance safe food delivery practices. The structural model and insights provide a valuable framework for developing targeted interventions and strengthening public health preparedness for future pandemics or similar crises.